Incidencia del clima laboral en el desempeño de los servidores públicos del Gobierno Autónomo Descentralizado Municipal de El Carmen, periodo 2022 - Loor Vera, Josselyn Jazmín (2023)
The present research was developed in the Municipal Decentralized Autonomous Government in El Carmen canton, in the first instance an interview was conducted with the Department of Human Talent to determine the current situation in relation to work performance, considering integral labor dimensions such as teamwork, leadership, physical space, motivation, orientation of results and feedback, allowing to obtain a general projection for the scope of the first objective, likewise, the institutional organic structure was represented based on the information obtained, in relation to the types of investigation, descriptive, exploratory and field supports, and the application of the investigative, analytical, inductive and deductive in the GADM facilities in El Carmen canton. After that, a diagnosis of the work environment was made on the influential factors, such as cohesion, pressure, innovation, equity, autonomy, recognition and support, which was carried out through the application of a survey to the public servants of the GADM in El Carmen canton, coding the results through the instrument of the Likert Scale, where, it was determined that the factors that have the most incidence on the work environment are "pressure" (working time, days off and work stress) and "equity" (favoritism on the bosses’ part). Finally, an improvement plan was proposed aimed at the results of the factors that resulted in the highest incidence of the GADM work climate in El Carmen canton.